Gankyrin as Potential Biomarker for Colorectal Cancer With Occult Liver Metastases - Wang, Chengxing; Li, Xiaoping; Ren, Liangliang; Ma, Changyi; Wu, Meimei; Liang, Weijun; Zhao, Jinglin; Li, Shangren; Tan, Qunying; Liao, Yuehua; Sun, Lixia; Zhang, Xin; et al. (Frontiers in Oncology, 2021)
The majority of occult liver metastases cannot be detected by computed tomography (CT), magnetic resonance imaging (MRI) or other traditionally morphological imaging approaches since the lesions are too small or they have not yet formed cancer nodules. Gankyrin is a small molecular protein composed of seven ankyrin domains. In this study, the expression of Gankyrin in colorectal cancer (CRC) patients with liver metastases was investigated to determine its prognosis value. Gankyrin expression in CRC patients was initially analyzed using data from The Cancer Genome Atlas (TCGA) database and bioinformatics tools. RT-qPCR, western blotting, immunohistochemistry (IHC) and transwell migration and invasion assays were then performed to verify the expression and function of Gankyrin in CRC cell line, CRC tissues and matched non-tumor tissues of clinical patients. General clinicopathological information including TNM stage as well as preoperative and postoperative imaging results were collected. The main outcome indicator was overall survival (OS), referring to the length of time from surgery to either death or the last visit. Statistical analyses included chi-squared tests, Cox analyses, progression free survival (PFS) rates and OS rates. Elevated Gankyrin expression was confirmed in CRC patients. The upregulated Gankyrin expression was positively correlated with the progression of disease and liver metastasis in CRC patients. OS analysis revealed that prognosis was worse in CRC patients with high Gankyrin expression compared to those with low expression. CRC patients with higher Gankyrin expression also had a higher risk of occult liver metastases and a lower PFS rate. Therefore, Gankyrin can be used as a potential biomarker for early diagnosis of CRC with occult liver metastasis.